2023
DOI: 10.3892/ijmm.2023.5287
|View full text |Cite
|
Sign up to set email alerts
|

RAS‑stimulated release of exosomal miR‑494‑3p promotes the osteolytic bone metastasis of breast cancer cells

Abstract: RAS activation is a key determinant of breast cancer progression and metastasis. However, the role of the interaction among exosomes, RAS and microRNAs (miRNAs/miRs) in the osteolytic bone metastasis of breast cancer remains unclear. Therefore, the present study aimed to examine the role of activated RAS (KRAS, HRAS and NRAS) in the release of exosome-mediated osteoclastogenic miRNAs and to elucidate their functional role in bone microenvironment remodeling in vitro and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Since then, SEMA3A has been well studied not only in axon guidance, but also in pleiotropic functions, including in angiogenesis, immune cell regulation and cell migration [6]. SEMA3A is expressed in kidneys, as well as the nervous system, heart, lung, eyes, bone and immune cells [7][8][9][10][11][12], and regulates tissue development and the maintenance of homeostasis, for example, through the regulation of cell proliferation and migration, and the immune system [13][14][15]. Several reports have identified an increase or decrease in SEMA3A expression under several disease conditions [16][17][18][19]; thus, SEMA3A has been suggested as a possible biomarker, as well as a therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, SEMA3A has been well studied not only in axon guidance, but also in pleiotropic functions, including in angiogenesis, immune cell regulation and cell migration [6]. SEMA3A is expressed in kidneys, as well as the nervous system, heart, lung, eyes, bone and immune cells [7][8][9][10][11][12], and regulates tissue development and the maintenance of homeostasis, for example, through the regulation of cell proliferation and migration, and the immune system [13][14][15]. Several reports have identified an increase or decrease in SEMA3A expression under several disease conditions [16][17][18][19]; thus, SEMA3A has been suggested as a possible biomarker, as well as a therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, Kim et al showed that RAS activation in BC cells triggered osteolytic bone metastasis by exciting exosome-mediated osteoclast production of miRNAs, including miR-494-3p, to osteoblasts. 17 This feature makes exosomal miRNAs derived from tumor tissue or other body fluids high-value indicators for tumor differential diagnosis, treatment monitoring, and prognosis evaluation. 18 Given the increasingly prominent roles of exosomal miRNAs in BC, here we highlight the novel roles and mechanisms of exosomal miRNAs, including BC progression regulation, as well as their roles in clinical BC diagnosis and treatment.…”
mentioning
confidence: 99%